EXPERIMENTAL ASSESSMENT OF THE PERFORMANCE OF REINFORCED CONCRETE BEAMS STRENGTHENED WITH CARBON FIBER REINFORCED POLYMER LAMINATES (Nigerian Journal of Technology, 2020)
In this study, experimental research is carried out to assess the flexural performance of RC beams strengthened with different amount of CFRP laminates at the tension face. Twelve rectangular RC beams were fabricated and three are un-strengthened and used as reference beams and the remaining nine are strengthened with different amount of CFRP varying from single to triple layers and all are tested to failure under three points bending test. The increase of ultimate strength provided by the bonded CFRP laminates is assessed and failure modes is identified and compared to the un-strengthened RC beams. The results indicated that the flexural capacity of the beams was significantly improved as the amount of the laminates increases that ranged from 20% to 52% increased for single to triple layers laminates. It is concluded that the attachment of CFRP laminates has substantial influence on the performance of CFRP strengthened RC beams. Based on the observed results, recommendations are made that externally application of CFRP laminates can be used for a significant enhancement of the strength deficient RC beams in increasing the ultimate load carrying capacity. http://dx.doi.org/10.4314/njt.v39i1.11